Institutional Determinants of Worker Flows A Cross-Country/Cross-Industry Approach - Bassanini, Andrea (OECD Social, Employment and Migration Working Papers, 2010)
There is little cross-country comparative evidence on the way labour market institutions shape gross job and worker flows, by and large because comparable data for many countries are scarce. By using a unique harmonised dataset on hirings and separations at the industry-level for a large majority of OECD countries, we fill this gap, by analysing the role of a number of labour and product market institutions in shaping cross-country differences in gross worker flows. In order to identify the effect of policies and institutions we consider an industry-level difference-in-difference approach. The basic premise of this approach is that the effect of a particular policy on gross job flows is greater in industries where the policy is more likely to constrain firm behaviour. We check, however, the robustness of our results using more standard cross-country/time-series estimates. The richness of the data available to us allows estimating the impact of the institutions also on the transitions from job to job, the transitions from job to nonemployment and the transitions from non-employment to jobs. We find that cross-country differences in job protection for open-ended contracts and unemployment benefits can explain a large share of crosscountry variation in gross worker flows. However, the effect of the former is essentially limited to job-tojob flows